Acoustic image log facies and well log petrophysical evaluation of the barra velha formation carbonate reservoir from the Santos Basin, offshore Brazil - Basso, Mateus, 1991- (2022)
Agradecimentos: The authors would like to thank Equinor for the productive partnership and financial support during this project, and for granting permission to publish this study. ANP is also acknowledged for the support and granting permission for publication. This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nivel Superior – Brasil (CAPES) – Finance Code 001. The authors are grateful for the important contributions by the anonymous reviewers. We are also grateful to Lloyd’s Register and Interactive Petrophysics (IP) software. Finally, special thanks to Francine Cristofoleti for the assistance with numerical data and to Raquel R. M. Cardoso for the language review. This study was supported by a governmental foundation of the Ministry of Education Brazil (CAPES) and by the energy company Equinor